Keda Mazbuut : a grammar book of Egyptian Arabic with exercises - Hassan, Mona Kamel (The American University in Cairo Press, 2020)
"An easy-to-use beginner's level guide to Egyptian Colloquial Arabic (ECA) grammar that is the ideal supplement for students. Keda Mazbuut is divided into twenty-five lessons, each devoted to a key grammatical rule, with examples to illustrate usage followed by a variety of exercises. Drawing on twenty-five years of experience as a full-time teacher of Arabic, Mona Hassan has organized the lesson topics to gradually progress in difficulty, from basic nominal sentences to more complex grammatical structures, such as the imperative and conditional sentences. All rules are explained in straightforward English, while words and phrases are provided in both Arabic script and transcribed Arabic, accompanied by audio files to facilitate students' ECA pronunciation. With its clear, user-friendly structure, Keda Mazbuut is designed to encourage students to work through grammatical rules at home, allowing them to devote more class time to the speaking activities that reinforce those rules"--Back cover